2009
DOI: 10.1007/s11664-009-0841-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Embrittlement Affecting the Impact Reliability of Tin-Based Lead-Free Solder Joints

Abstract: This work addresses a new mode of brittle failure that occurs in the bulk of tin-based lead-free solder joints, unlike the typical brittle failures that occur in the interfacial intermetallics. Brittle failures in the joint bulk result from the low-temperature ductile-to-brittle transition in the fracture behavior of b-tin. The bulk embrittlement of these joints is discussed by referring to the results of impact tests performed on both solder joints and bulk solder specimens. The mechanism of bulk embrittlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Through a large number of experiments, researchers have found that when the temperature gradually decreases, the ductile fracture strength of different solder material significantly increases [29]. When the temperature reaches the transition temperature range, the fracture characteristic of solders changes obviously, as well as the energy required for fracture.…”
Section: Methodsmentioning
confidence: 99%
“…Through a large number of experiments, researchers have found that when the temperature gradually decreases, the ductile fracture strength of different solder material significantly increases [29]. When the temperature reaches the transition temperature range, the fracture characteristic of solders changes obviously, as well as the energy required for fracture.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we focused on the ductile to brittle transition (DBTT) of pure Sn, using Insitu micromechanical testing to probe the deformation mechanisms above and below the DBTT 1 . Since Sn is the major constituent of most solders used in industry, our first study focused on the pure Sn with no other alloy element present given that the body centered tetragonal (bct) crystal structure β-Sn dictates the global mechanical properties of most solders 2 . The bct structure gives rise to several unique deformation mechanisms that change as a function of temperature, strain rate and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…These joints provide both electrical connections and mechanical support for the electrical package. Differences in the thermal expansion coefficients of materials used in electronic packaging cause cyclical strains in the solder joints upon thermal cycling [1][2] . Reliability of the solder joint depends upon a number of mechanical and microstructural evolutionary processes that occur interactively during its service lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, for studying the response of solder joints to dynamic loading at low temperatures, Ong et al (2004) performed a series of high‐speed cyclic bend tests to report a sharp change in the 98.9Sn‐1Ag‐0.1Cu (SAC101) solder joint failure from ductility at RT to brittleness at −10°C. Lambrinou et al (2009) conducted a board‐level impact assessment employing a miniature Charpy test, conducting observations of the brittle failure of Sn‐based and Pb‐free solders at low temperatures. The results demonstrated that low‐temperature embrittlement affected the impact reliability of solder joints.…”
Section: Introductionmentioning
confidence: 99%